A comparison of the ontogeny of the digestive system and growth of juvenile diploid and triploid Atlantic salmon (Salmo salar L.) fed a standard diet and an experimental diet containing high proportions of hydrolysed proteins - Ulleberg, Lars Olav (UiT The Arctic University of Norway, 2017)
The purpose of the study was to evaluate and compare the effect of different diets on the gut structure of diploid and triploid juvenile Atlantic salmon (Salmo salar), and analyze the overall performance in terms of growth and survival from hatch until the end of smoltification. At the beginning of the experiment, fish were divided into two groups, one diploid group and one triploid group. Four weeks after start feeding the fish were divided into four groups, two groups of different ploidy fed a standard diet, whereas the other two groups fed an experimental diet in which 45% of fishmeal (FM) fraction was replaced with hydrolysed proteins. The triploid fish fed standard diet (group 3) were the best performing after the initial phase and throughout the end of the experiment, both in terms of growth and survival. The diploid and triploid fish fed standard diet (group 1 and 3) were also superior in terms of survival compared to the fish fed experimental diets (group 2 and 4). Comparisons of the ontogeny of the digestive system between groups with respect to ploidy and diet revealed no obvious differences despite some variable trends. Under the present experimental conditions, the same conclusions can be drawn for the histomorphological traits measured in the digestive organs of these fish that were overall comparable. Results in present work show that the use of experimental diets containing high levels of hydrolysed proteins overall did support but not enhanced growth in triploid or diploid salmon from start feeding until the end of the smoltification process.